Glucocorticoid Abnormalities in Female Rats Exposed to a Predator-Based Psychosocial Stress Model of PTSD - Zoladz, Phillip R.; Del Valle, Colin R.; Smith, Ian F.; Goodman, Cassandra S.; Dodson, Jordan L.; Elmouhawesse, Kara M.; Kasler, Charis D.; Rorabaugh, Boyd R. (Frontiers in Behavioral Neuroscience, 2021)
People with post-traumatic stress disorder (PTSD) exhibit heightened anxiety and enhanced negative feedback of the hypothalamus-pituitary-adrenal (HPA) axis. We previously reported that male rats exposed to a predator-based psychosocial stress model of PTSD exhibited comparable changes in anxiety-like behavior and HPA axis activity, including lower baseline levels of corticosterone and a greater suppression of corticosterone after dexamethasone administration. Here, we assessed whether we would observe similar effects in female rats exposed to this model. Adult female Sprague-Dawley rats were exposed to a cat on two occasions (separated by 10 days), in combination with chronic social instability. Three weeks after the second cat exposure, we assessed anxiety-like behavior on an elevated plus maze (EPM) and collected blood samples from rats in the absence or presence of dexamethasone to quantify serum corticosterone levels. Although stressed females did not display heightened anxiety on the EPM, they exhibited significantly lower overall corticosterone levels and a greater suppression of corticosterone after dexamethasone administration. The observation of significantly lower overall corticosterone levels in stressed females was replicated in a separate, independent experiment. These findings suggest that the predator-based psychosocial stress model of PTSD may be useful for studying mechanisms that underlie changes in HPA axis function in females exposed to trauma.